Persahabatan Antara Allah Dan Manusia: Suatu Tinjauan Alkitabiah - Henricus Pidyarto Gunawan (Seri Filsafat Teologi, 2020)
When God communicates with human, He needs to use human language and ideas. God, in one way and another, is described as human’s friend. This is called anthropomorphism. The friendship among people is difinetely noble and beautiful that it is appropriate to describe the relationship between God and human. This relationship becomes very obvious from the explicit verses about God’s friends as well as from the similarity in the terms used in both friendships.